CENTRAL BANK DIGITAL CURRENCY IN THE REPUBLIC OF UZBEKISTAN - Akhmadaliyeva Nikholakhon; Narzikulov Sardorbek (The Conference Hub, 2025)
The global march towards Central Bank Digital Currencies (CBDCs) has accelerated, with numerous nations now in advanced pilot or launch stages. For the Republic of Uzbekistan, a nation demonstrating robust economic growth and a strong commitment to digital transformation, the strategic implementation of a CBDC the “Digital Sum” is a critical next step. This thesis constructs a comprehensive, evidence-based framework for a retail CBDC tailored to Uzbekistan's contemporary economic landscape. Analyzing the latest data from 2024-2025, the research highlights how a CBDC can directly address the persistent shadow economy1, enhance a financial inclusion rate that has improved but still has gaps, and modernize a payment system undergoing rapid change. By evaluating the most recent lessons from global pioneers like China's e-CNY, India's digital rupee, and the Eastern Caribbean DCash, this thesis proposes a specific two-tier, hybrid CBDC model. The study concludes that a carefully designed Digital Sum, implemented through a phased roadmap, can serve as a powerful catalyst for financial formalization, monetary policy innovation, and sustainable, inclusive economic growth in Uzbekistan.
Keywords: Central Bank Digital Currency (CBDC), Digital Sum, Uzbekistan, Financial Inclusion, Shadow Economy, Digital Payments, Monetary Policy.